The Costs of Recruitment and Retention of Women from Community-Based Programs into a Randomized Controlled Contraceptive Study - Rdesinski, Rebecca E; Melnick, Alan L; Creach, E. Dawn; Cozzens, Jessica; Carney, Patricia A (Journal of health care for the poor and underserved, 2008)
Study aim . Assessing recruitment and retention activities needed to enroll women identified through community-based programs (such as the Women, Infants, and Children (WIC) program) into a randomized controlled clinical trial on nurse-delivered contraceptives in the home. The majority of women in this study had low socioeconomic status indicators and low levels of education, and the majority were young. Methods . Recruitment sources and number of contact-attempts were collected and analyzed. Full time equivalents needed to undertake these activities were estimated. Results . Two hundred and forty five women were identified in recruiting and enrolling 103 study participants involving 1,232 contact-attempts. Self-referral had the highest ratio of referrals to enrollees (55.6%), while this ratio was the lowest for community outreach (33.3%). Retention activities succeeded in maintaining over 90% of the sample. Ninety-two percent of English-speaking participants completed the study versus 79% of Spanish-speaking participants. The time expenditure per enrollee was 10.4 hours for recruitment and 1.2 hours for retention, with an estimated cost per enrollee of $324.03 for recruitment and $39.14 for retention. More retention activities were required to maintain women in the comparison group than in the intervention group.